Reuse of Residual Biomass of Cellulose Industry for Second Generation Bioethanol Production - Junior, Nei Pereira; Moraes, Anelize de Oliveira; Modesto, Luiz Felipe; Ramirez, Ninoska Isabel Bojorge (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
This study aimed at evaluating the potential of pulp mill residue (PMR) as a feedstock for ethanol production. The simultaneous saccharification and fermentation (SSF) process was operated using 8 gL -1 of a commercial strain of Saccharomyces cerevisiae JP1 under optimal proportions of cellulase cocktail (24.8 FPU/g cellulose of Cellic CTec2) and cellulosic residue (200 gL -1 ). After 48 hours of pre-hydrolysis at 50ºC and 200 rpm, the fermentation was carried out at 37ºC, generating 48.5 gL -1 of ethanol in 10 hours and reaching a conversion efficiency of 53.3% from cellulose to ethanol and a volumetric productivity of 4.8 gL -1 h -1 that is within the range of values of first generation ethanol production (5-8 gL -1 h -1 ). These results showed that the pulp mill residue is an interesting and effective feedstock for the production of ethanol, which can be used for fuel purposes in the own pulp mills.